2007
DOI: 10.1007/s00209-007-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

Trees and hairs for some hyperbolic entire maps of finite order

Abstract: Let f be an entire transcendental map of finite order, such that all the singularities of f −1 are contained in a compact subset of the immediate basin B of an attracting fixed point. It is proved that there exist geometric coding trees of preimages of points from B with all branches convergent to points from C. This implies that the Riemann map onto B has radial limits everywhere. Moreover, the Julia set of f consists of disjoint curves (hairs) tending to infinity, homeomorphic to a half-line, composed of poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 21 publications
1
69
0
2
Order By: Relevance
“…After our proof of Theorem 1.2 was first announced, Barański [Bar07] independently obtained a proof of this result for hyperbolic finite-order functions f ∈ B whose Fatou set consists of a single basin of attraction. (In fact, Barański showed that for these functions every component of the Julia set is a curve to ∞; compare Theorem 5.10.)…”
Section: Corollary (Meromorphic Functions With Logarithmic Singularitmentioning
confidence: 99%
See 1 more Smart Citation
“…After our proof of Theorem 1.2 was first announced, Barański [Bar07] independently obtained a proof of this result for hyperbolic finite-order functions f ∈ B whose Fatou set consists of a single basin of attraction. (In fact, Barański showed that for these functions every component of the Julia set is a curve to ∞; compare Theorem 5.10.)…”
Section: Corollary (Meromorphic Functions With Logarithmic Singularitmentioning
confidence: 99%
“…Let us also say that F is of disjoint type if T ⊂ H. It is easy to see that a function f ∈ B has a disjoint-type logarithmic transform if and only if S(f ) is contained in the immediate basin of an attracting fixed point of f . (This is the setting considered by Barański [Bar07].) Note that we might not be able to normalize such a function in the above-mentioned manner without losing the disjoint-type property.…”
Section: The Eremenko-lyubich Class B and The Class B Logmentioning
confidence: 99%
“…Proof of Theorem 5.8 (2). Since A, H ≥ 2, we have that 1 1 + h x : h x α < 1/4 ⊂ C x , for all x ∈ X.…”
Section: Lemma 82 There Exists a Constantmentioning
confidence: 89%
“…In contrast to the case of hyperbolic rational functions, the dynamics of a general hyperbolic transcendental function on the Julia set can not be represented by a symbol dynamics. However, some particular entire functions act on a dynamically important subset of the Julia set, the so called set of "landing-" or "end-"points, in a similar way as countable Markov shifts that we consider in here (see [2,3]). …”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation